Avaliação da maturidade de processos de uma empresa prestadora de serviços de telecomunicação, sob o enfoque do método PEMM - Silveira, Lyla Paula (2021)
Mature organizations follow standards and operationalize their processes in a systematic way, resulting in operational efficiency and competitive advantage. The methods developed to assess the maturity of processes are intrinsically linked to the concepts that characterize mature organizations, allowing organizations to access methodologies that help assess their processes and implement improvements. In this perspective, the objective of this case study is to evaluate the maturity of processes of a telecommunications service provider company. For the research, the PEMM (Process Enterprise Capability Model) method was used, proposed by Michael Hammer, which performs the analysis of process maturity based on process enablers and organizational capabilities. For data collection, questionnaires were used, in which the results can vary between levels P0 and P4 for process enablers, and between levels E0 and E4 for organizational capabilities. The maturity levels reached by the organization were P0 and E0. In the research, potential factors and inhibitors of the organizational maturity level were identified, in addition to proposing actions to promote the development of organizational maturity and raise current levels